Audit committee characteristics and risk management of Malaysian listed firms / Puan Yatim - Yatim, Puan (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
This study explores the association between audit committee characteristics and the establishment of a risk management committee by Malaysian listed firms. The study predicts that firms with more independent, expert, and diligent audit committees are likely to establish a stand-alone risk management committee. It is also expected that audit committees with more members are also likely to support the establishment of a risk management committee. The study employs a cross-sectional analysis of 690 firms listed on the Bursa Malaysia for the financial year ending in 2003. A logistic regression analysis is used to estimate the relationships proposed in the hypotheses. The study finds a strong support for an association between the establishment of risk management committee and audit committee independence, audit committee size, and audit committee diligence. The results also show that the establishment of a risk management committee is positively and significantly associated with firm-specific variables such as firm size, complexity of a firm’s operations, and the use of Big Four audit firms